Entomological studies for the surveillance of dengue in Iran, 2006–2016 - Mohammad Reza Shirzadi (Biomedical and Biotechnology Research Journal, 2019)
Dengue is the most quickly distributing mosquito-borne disease caused by flaviviruses. The mosquito Aedes aegypti is the essential vector for disease transmission. The aim of this report was to describe dengue in Iran. In 2006, the Ministry of Health of Iran conducted a coordinated series of meetings with the Ministry of Agriculture of Iran about the correct way of importing the lucky bamboo and other agricultural products. The Ministry of Health of Iran coordinated with the Department of Arbovirus of Pasteur Institute of Iran to investigate the human samples in cases suspected for dengue disease. In 2013, the guideline to control the dengue was prepared in the center for communicable diseases control, Ministry of Health and Medical education, Iran. In 2014, an operational program to disease control was prepared. A network of laboratories to entomological surveillance was established in 2014. The credit for equipping of entomology laboratories was provided. In 2015, a national plan for the prevention and control of dengue was prepared in the English language and with the WHO cooperation. Other plans such as preparation of the health messages about dengue and sending them to the medical universities were done. The surveillance activities against dengue were defined in three levels, including surveillance in the cities, surveillance in the provinces, and surveillance in the country. Other follow-up actions included planning for continued educational program for dengue in different universities of medical sciences, equipping of the entomology laboratories of the universities, and conducting the entomological checks and educational activities of the universities.